Magnetic equivalent circuit model of a hybrid excitation synchronous machine - Hlioui, S.; Vido, L.; Amara, Y.; Gabsi, M.; Miraoui, A.; Lécrivain, M. (Compel, 2008)
Purpose - The purpose of this paper is to present an analytical modeling based on lumped parameter magnetic circuits of a hybrid excitation synchronous machine. The model is first established and compared with 3D finite elements analysis and measurements. It is then used to optimise hybrid excitation effectiveness.Design methodology approach - The machine studied, which has a 3D structure, requires the use of 3D finite elements method. The 3D FEA tool is still time-consuming, which limits its use in optimal design process. To overcome this limitation the paper investigates an analytical modeling based on lumped parameter magnetic circuits. The developed model is then used in an optimisation procedure.Findings - The machine presented has an original structure. It has been subject to a patent protection. The operating principle of this structure has been presented and optimisation of hybrid excitation effectiveness has been investigated. Double excitation allows one to control air gap flux while reducing permanent magnets' demagnetisation risk.Originality value - The paper presents an original structure with true field regulation capability. The principle of operation has been presented. A prototype has been built and tested. The paper also presents a 3D finite elements analysis of this machine and an analytical modelling.